Establishment of concurrence between peer and teacher evaluations - Bes-Mariano, Maria Ana M. (2002)
With recent developments in medical education affording both the academe and the students an easy access to all possible information there has been a transformation of their traditional roles as teachers and students to that of collaborators in learning. In addition, there is a need to reform evaluation of performance in medical education that puts overemphasis to facts with very little meaningful learning. Thus the need to involve students in assessing performance in preparation for their future roles as health professionals and in making them more responsible for their learning. The purpose of this study is to compare peer and teacher evaluations in assessing student performance in the three domains of learning: knowledge, skills and attitudes and to establish in which domain(s) do they concur. Once proven that they concur, students would be recognized as capable of their own learning and could help evaluate their competence. An evaluation tool for small group learning activities using a Likert scale was developed and adapted for the use of peers and teachers evaluating student performance in two case discussions in Physiology. All first year medical students in Pamantasan ng Lungsod ng Maynila and all faculty of the Department of Physiology during school year 2000-2001 participated in this study. Descriptive statistics were used to summarize data and provide a profile of the respondents. The t-test for unmatched pairs was used to establish concurrence between teacher and peer raters. Results showed that both raters do not concur in assessing knowledge, skills and attitudes. Teacher raters tend to give lower ratings compared to peer raters who gave higher ratings in all learning domains with the highest ratings in attitudes. Students concurred with teachers in distinguishing the same level of student performance in certain areas of the learning domains: knowledge (comprehension, synthesis and recall), skills (communication and organizing skills) and attitudes (attitudes to peers). On this basis peer rating is a potential source of evaluation. Rater characteristics, time constraints, group size, composition and dynamics, facilitating styles, group dynamics and the type of case studies discussed were factors which affected how they rated differently in this study.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Teachers -- Rating of; Peer review